2017
DOI: 10.1016/j.jneuroim.2017.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Untreated relapsing remitting multiple sclerosis patients show antibody production against latent Epstein Barr Virus (EBV) antigens mainly in the periphery and innate immune IL-8 responses preferentially in the CNS

Abstract: These findings in newly diagnosed RRMS-patients imply anti-EBNA-1 antibody production mainly in the periphery and innate immune responses preferentially in the CNS. Both their potential as disease biomarkers and their implications for the pathogenesis of MS warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Proinflammatory cytokines TNFa, IL-1b, and IL-6, as well as increased reactive oxygen species (ROS) and reactive nitrogen species, can be injurious to healthy cells and are commonly seen in brain or cerebrospinal fluid of individuals suffering CNS disease, including HIVE. [27][28][29] In our study, both HIV groups demonstrated altered transcripts related to immune activation including the proinflammatory cytokines IL-1b and IL-6, and the major TNFa receptor Tnfrsf1a. Increased transcription of IL-6 and Tnfrsf1a supports our earlier immunohistochemical findings within the same subjects that show substantial widespread microglial activation in HIV, including individuals on cART prior to death and without detectable virus in brain.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Proinflammatory cytokines TNFa, IL-1b, and IL-6, as well as increased reactive oxygen species (ROS) and reactive nitrogen species, can be injurious to healthy cells and are commonly seen in brain or cerebrospinal fluid of individuals suffering CNS disease, including HIVE. [27][28][29] In our study, both HIV groups demonstrated altered transcripts related to immune activation including the proinflammatory cytokines IL-1b and IL-6, and the major TNFa receptor Tnfrsf1a. Increased transcription of IL-6 and Tnfrsf1a supports our earlier immunohistochemical findings within the same subjects that show substantial widespread microglial activation in HIV, including individuals on cART prior to death and without detectable virus in brain.…”
Section: Discussionsupporting
confidence: 49%
“…Microglia have been implicated as key players in promoting and advancing neurodegenerative disease, largely through immune activation and associated soluble factors that are directly or indirectly neurotoxic. Proinflammatory cytokines TNFα, IL‐1β, and IL‐6, as well as increased reactive oxygen species (ROS) and reactive nitrogen species, can be injurious to healthy cells and are commonly seen in brain or cerebrospinal fluid of individuals suffering CNS disease, including HIVE . In our study, both HIV groups demonstrated altered transcripts related to immune activation including the proinflammatory cytokines IL‐1β and IL‐6 , and the major TNFα receptor Tnfrsf1a .…”
Section: Discussionmentioning
confidence: 64%
“…While the negative effects of sporadic or continuous CMV replication are well-known, there is still uncertainty on the role of EBV in favoring chronic immune activation. Neuroinflammation, neurodegeneration and its drivers are widely studied in MS and Late EBV infection seemed to be one of the risk factors involved in promoting the initial events and the relapses of this chronic neurological condition [41][42]. In most CSF of MS patients were founded elevated antibody levels against the entire EBV nuclear antigen (EBNA), and EBNA-1, a protein expressed during latent EBVinfection [43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Since EBNA1 is widely expressed in EBV infected cells [46], it is intriguing to speculate that its splicing activity has a role in the trans splicing that has been postulated to produce functional MSRV env molecules [17]. This adds to the many different mechanisms proposed to explain why EBV infections are a predisposition for MS [1][2][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors, e.g. vitamin D deficiency [4], and infections especially with Epstein Barr virus (EBV) [1][2][5][6][7][8], have been implicated in predisposition to MS. Genome-wide association studies demonstrate that the HLA Class II allele DRB1*1501 β chain variant, which pairs with the relatively invariant DRA1*0101 α chain to form the HLA DR2b heterodimer in antigen-presenting cells (APCs), is the strongest genetic risk factor for MS [9]. The production of virions and expression of envelope protein (env) of a member of the genome-encoded human endogenous retrovirus W-family (HERV-W), termed the MS-associated retrovirus or MSRV [10], has also been implicated in MS [11 -15].…”
Section: Introductionmentioning
confidence: 99%